Advanced database query systems : techniques, applications and technologies - Yan, Li, 1964-; Ma, Zongmin, 1965- (Hershey PA : Information Science Reference, 2011)
'This book focuses on technologies and methodologies of database queries, XML and metadata queries, and applications of database query systems, aiming at providing a single account of technologies and practices in advanced database query systems'--Provided by publisher.
Includes bibliographical references and index.
Keywords: Databases; Query languages (Computer science); Querying (Computer science)